Starting a Fire Without Flame: The Induction of Cell Death and Inflammation in Electroporation-Based Tumor Ablation Strategies - Brock, Rebecca M.; Beitel-White, Natalie; Davalos, Rafael V.; Allen, Irving C. (Frontiers in Oncology, 2020)
New therapeutic strategies and paradigms are direly needed for the treatment of cancer. While the surgical removal of tumors is favored in most cancer treatment plans, resection options are often limited based on tumor localization. Over the last two decades, multiple tumor ablation strategies have emerged as promising stand-alone or combination therapeutic options for patients. These strategies are often employed to treat tumors in areas where surgical resection is not possible or where chemotherapeutics have proven ineffective. The type of cell death induced by the ablation modality is a critical aspect of therapeutic success that can impact the efficacy of the treatment and systemic anti-tumor immune system responses. Electroporation-based ablation technologies include electrochemotherapy, irreversible electroporation, and other modalities that rely on pulsed electric fields to create pores in cell membranes. These pores can either be reversible or irreversible depending on the electric field parameters and can induce cell death either alone or in combination with a therapeutic agent. However, there have been many controversial findings among these technologies as to the cell death type initiated, from apoptosis to pyroptosis. As cell death mechanisms can impact treatment side effects and efficacy, we review the main types of cell death induced by electroporation-based treatments and summarize the impact of these mechanisms on treatment response. We also discuss potential reasons behind the variability of findings such as the similarities between cell death pathways, differences between cell-types, and the variation in electric field strength across the treatment area.